2015
DOI: 10.1007/s12043-014-0882-7
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional polynomials and SUSY quantum mechanics

Abstract: We show that the existence of exceptional polynomials leads to the presence of non-trivial supersymmetry. The existence of these polynomials reveals several distinct isospectral potentials for the Schrödinger equation. All Schrödinger equations having Laguerre and Jacobi polynomials as their solutions, have non-trivial supersymmetric partners with corresponding exceptional polynomials as solutions. * 1 chaitanya@imsc.res.in, 3 pprasanta@iiserkol.ac.in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Thus it leads to different kind of SUSY between the two partners. This is called as nontrivial supersymmetry [18]. Similar situations were encountered in the past, where isospectral deformation lead to non-shape invariant partners, but in these cases only few eigenfunctions could be calculated analytically for the deformed partner [37], [42].…”
Section: Nontrivial Supersymmetry and Conventional Supersymmetrymentioning
confidence: 91%
See 1 more Smart Citation
“…Thus it leads to different kind of SUSY between the two partners. This is called as nontrivial supersymmetry [18]. Similar situations were encountered in the past, where isospectral deformation lead to non-shape invariant partners, but in these cases only few eigenfunctions could be calculated analytically for the deformed partner [37], [42].…”
Section: Nontrivial Supersymmetry and Conventional Supersymmetrymentioning
confidence: 91%
“…Using the above equations, we can construct an hierarchy of ES potentials and their solutions from V − (x) and its solutions. The existence of the rational potentials has led to the idea of SUSY being nontrivial [18], which will be elaborated in the later sections.…”
Section: Supersymmetric Quantum Mechanicsmentioning
confidence: 99%
“…The hypergeometric polynomials, {}pn()x, orthogonal with respect to the weight function h()x on the support interval normalΛ, are known to often control the quantum‐mechanical wavefunctions of the bound states in numerous quantum systems [14, 39–43]. The Hermite, Laguerre and Jacobi polynomials are the three canonical families of real HOPs [44–47].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Different methods like the Darboux-Crum method, 9,10 finite difference Backlünd algorithm, [11][12][13] prepotential method 14 and several others 15,16 were employed. Various groups explored the mathematical properties of the new polynomials concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…Various groups explored the mathematical properties of the new polynomials concurrently. [19][20][21] Many studies showed that the traditional SIPs and their rational extensions are isospectral and share a supersymmetric partnership 3,15,16 and that the superpotentials of the traditional SIPs play a pivotal role. Now that the dust has settled over the construction of these new potentials, we think there is a need for a method, which is transparent, systematic and elegant.…”
Section: Introductionmentioning
confidence: 99%